IMPLEMENTING MOBIL-ASSISTED LANGUAGE LEARNING (MALL) TOWARD AUTONOMOUS LEARNERS IN WRITING CLASS - Enni Erawati Saragih; Alan Jaelani (STKIP PGRI Jombang, 2020)
The widespread in accessing mobile phone changed the way people learning. Dealing with the rapid growth of technology, Mobile-assisted language learning (MALL) becoming popular because of the portability. MALL is characterized by its potential for learning to be spontaneous, informal, personalized, and ubiquitous. Two main discussions were analyzed in the research; to investigate the implementation of MALL and to know students perspective on Using MALL in writing class. Classroom action research applied in the research, in which observation and interview were used as instruments in collecting the data. The research result shown that MALL were able to be implemented in writing class, it facilitated the students to express their idea and feeling in writing with online board platform such as Padlet.